PRAK, a novel protein kinase regulated by the p38 MAP kinase. - New, L (1998)
We have identified and cloned a novel serine/ threonine kinase, p38-regulated/activated protein kinase (PRAK). PRAK is a 471 amino acid protein with 20-30% sequence identity to the known MAP kinase-regulated protein kinases RSK1/2/3, MNK1/2 and MAPKAP-K2/3. PRAK was found to be expressed in all human tissues and cell lines examined. In HeLa cells, PRAK was activated in response to cellular stress and proinflammatory cytokines. PRAK activity was regulated by p38alpha and p38beta both in vitro and in vivo and Thr182 was shown to be the regulatory phosphorylation site. Activated PRAK in turn phosphorylated small heat shock protein 27 (HSP27) at the physiologically relevant sites. An in-gel kinase assay demonstrated that PRAK is a major stress-activated kinase that can phosphorylate small heat shock protein, suggesting a potential role for PRAK in mediating stress-induced HSP27 phosphorylation in vivo.